"Enervare atque pervertere verba illa Christi Matthaei 11": Arguing over Matthew 11:21–22 in Luis de Molina’s (1535–1600) Concordia and Leonardus Lessius’ De gratia efficaci - Bruijn, Niels de (2024)
In the second half of the sixteenth century, the Jesuits Luis de Molina (1535-1600) and Leonardus Lessius (1554-1623) had been forced to defend their views on grace, free will and predestination against multiple attacks by fellow Catholic theologians. By comparing Molina’s commentaries on Matt 11:21-22 in his Concordia of 1595 with Lessius’ remarks on the same verses in his De gratia efficaci (1610), this contribution seeks to provide insights into the extent to which the theological views of both Jesuits differed. The article concludes that Lessius’ theological view diverges from Molina’s where it concerns the physical workings of grace. Furthermore, the two Jesuits differ on the question whether God grants equal aid to all or bestows some with more aid than others. Molina held the latter view, while Lessius, in keeping with the ideas of Henry of Ghent, defended the former.
Keywords: Jesuits; Grace; Middle Knowledge; Predestination; Soteriology